2014
DOI: 10.1007/s13361-014-0877-0
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Strategies to Improve the Identification of Pt(II)-Modification Sites on Peptides and Proteins

Abstract: To further explore the binding chemistry of cisplatin (cis-Pt(NH3)2Cl2) to peptides and also establish mass spectrometry (MS) strategies to quickly assign the platinum-binding sites, a series of peptides with potential cisplatin binding sites (Met(S), His(N), Cys(S), disulfide, carboxyl groups of Asp and Glu, and amine groups of Arg and Lys, were reacted with cisplatin, then analyzed by electron capture dissociation (ECD) in a Fourier transform ion cyclotron resonance mass spectrometer (FT-ICR MS). Radical-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…The samples were diluted to 5 μM with 20% methanol/0.1% formic acid immediately before MS analysis. Cisplatin, a moderately toxic compound, should be handled carefully in a safe environment, and the material safety data sheets should be studied carefully …”
Section: Methodsmentioning
confidence: 99%
“…The samples were diluted to 5 μM with 20% methanol/0.1% formic acid immediately before MS analysis. Cisplatin, a moderately toxic compound, should be handled carefully in a safe environment, and the material safety data sheets should be studied carefully …”
Section: Methodsmentioning
confidence: 99%
“…[78,79] A combination of different fragmentation techniques (CID and ECD) as well as ion mobility mass spectrometry (IM-MS) allowed the determination of the sulfur atom of the methionine residue of substance P as the favoured binding site of cisplatin, whereas the His residues of angiotensin II and bombesin appeared to be preferred. [78][79][80] Tandem mass spectrometry techniques have been used to characterize cisplatin interactions with were recorded and showed that, even though the interactions between the complexes and the DNA strands were non-covalent in nature, they were strong enough to be observed in the gas phase during the analysis, and confirmed that PPCs do significantly stabilise the duplex structure of the oligonucleotide strands.…”
Section: Platinum Complexesmentioning
confidence: 99%
“…83 Both gas-phase dissociative approaches were utilized to study metallodrug-peptide complexes and characterize the amino acid binding sites. 84,85 CID, ETD, and higher-energy C-trap dissociation (HCD) were also applied to study a metallodrug-protein complex (i.e., the oxaliplatin-ubiquitin assembly). 86 Among the three approaches, ETD was the most useful for identifying the metal binding sites.…”
Section: Protein2ligand Interactions Studied By Fourier Transform Basmentioning
confidence: 99%
“…CID and ECD were also used to characterize nanoscale bilayers (nanodiscs) formed by the binding of phospholipids to a scaffold protein . Both gas‐phase dissociative approaches were utilized to study metallodrug‐peptide complexes and characterize the amino acid binding sites . CID, ETD, and higher‐energy C‐trap dissociation (HCD) were also applied to study a metallodrug‐protein complex (i.e., the oxaliplatin‐ubiquitin assembly) .…”
Section: Introductionmentioning
confidence: 99%